Postprandial fatty acid metabolism in the development of lipotoxicity and type 2 diabetes - Carpentier, André C. (Diabetes & metabolism, 2008)
Insulin resistance (IR) and impaired glucose-stimulated insulin secretion (GSIS) are the two primary pathophysiological abnormalities leading to the development of type 2 diabetes (T2D). Over the past two decades, a large body of work has implicated enhanced delivery of fatty acids to non-adipose tissues in the development of both IR and impaired GSIS. As the net whole-body import of fatty acids occurs in the postprandial state, tissue fatty acid overexposure has been linked to this physiological state. Although many advances have been made in our understanding of these lipotoxic effects at the cellular level, the precise mechanisms of lipotoxicity at the whole-body level in humans during the development of T2D is still a subject of debate. Important advances continue to be made in our understanding of the mechanisms that regulate postprandial fatty acid delivery to tissues and their metabolism. This review focuses on those mechanisms and on the potential implication of their dysregulation for tissue lipotoxicity in the development of T2D. La résistance à l’insuline et la diminution de la sécrétion d’insuline stimulée par le glucose sont les deux principales anomalies physiopathologiques qui sous-tendent le diabète de type 2. Au cours des deux dernières décennies, un grand nombre de travaux de recherche ont souligné l’importance de l’exposition excessive des tissus aux acides gras dans le développement de la résistance à l’insuline de même que la diminution de sécrétion de l’insuline. Puisque l’importation nette d’acides gras se produit en période postprandiale, la surexposition tissulaire aux acides gras survient lors de cette période physiologique. Bien des avancées ont été effectuées dans notre compréhension des mécanismes cellulaires toxiques qui surviennent lors de la surexposition des tissus aux acides gras. Cependant, les mécanismes mis en jeu au niveau du corps entier chez l’humain pendant l’évolution vers le diabète de type 2 ne sont pas totalement élucidés. Des avancées récentes qui permettent de mieux comprendre les mécanismes qui régulent le transport des acides gras aux tissus ainsi que leur métabolisme sont revues dans cet article. L’implication de leurs anomalies dans l’installation de la lipotoxicité tissulaire et le développement du diabète de type 2 est discutée.